Circulating Tumor Cells (CTCs): A Unique Model of Cancer Metastases and Non-invasive Biomarkers of Therapeutic Response - Liu, Jialing; Lian, Jingru; Chen, Yafei; Zhao, Xin; Du, ChangZheng; Xu, Yang; Hu, Hailiang; Rao, Hai; Hong, Xin (Frontiers in Genetics, 2021)
Late-stage cancer metastasis remains incurable in the clinic and is the major cause death in patients. Circulating tumor cells (CTCs) are thought to be metastatic precursors shed from the primary tumor or metastatic deposits and circulate in the blood. The molecular network regulating CTC survival, extravasation, and colonization in distant metastatic sites is poorly defined, largely due to challenges in isolating rare CTCs. Recent advances in CTC isolation and ex vivo culture techniques facilitates single-cell omics and the development of related animal models to study CTC-mediated metastatic progression. With these powerful tools, CTCs can potentially be used as noninvasive biomarkers predicting therapeutic response. These studies may open a new avenue for CTC-specific drug discoveries. In this short review, we aim to summarize recent progress in the characterization of CTCs and their clinical relevance in various cancers, setting the stage for realizing personalized therapies against metastases.